Comparative Study of Surface-Active Properties and Antimicrobial Activities of Disaccharide Monoesters - Zhang, Xi; Song, Fei; Taxipalati, Maierhaba; Wei, Wei; Feng, Fengqin (PLOS ONE, 2014)
The objective of this research was to determine the effect of sugar or fatty acid in sugar ester compounds on the surface-active properties and antimicrobial activities of these compounds. Disaccharides of medium-chain fatty acid monoesters were synthesized through transesterifications by immobilized lipase (Lipozyme TLIM) to yield nine monoesters for subsequent study. Their antimicrobial activities were investigated using three pathogenic microorganisms: Staphylococcus aureus, Escherichia coli O157:H7 and Candida albicans. Their surface-active properties including air–water surface tension, critical micelle concentration, and foaming and emulsion power and stability were also studied. The results showed that all of the tested monoesters were more effective against Staphylococcus aureus (Gram-positive bacterium) than against Escherichia coli O157:H7 (Gram-negative bacterium). The results demonstrated that the carbon chain length was the most important factor influencing the surface properties, whereas degree of esterification and hydrophilic groups showed little effect.